2019
DOI: 10.24002/kinerja.v23i2.2417
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Leadership: Charismatic Characteristics of Sri Lankan School Teachers

Abstract: This study identifies a number of charismatic leadership characteristics of school teachers in Sri Lanka. Since charisma is an instrumental asset in any work context, leaders’ charismatic characteristics can make extraordinary effects on follower toward mission accomplishment. In the teaching-learning context, teachers are viewed as great leaders that make magnificent transformations in the students. A teacher becomes the leader in the classroom as well and they are playing a significant role to build a cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Sufficient empirical evidence is available to support that teachers are the most crucial in-school factor for student learning (Berry, 2013;Clotfelter et al, 2010). Based on leadership theory, Gunasekare (2019) found that the characteristics of teachers with charismatic leadership include setting tasks for students, unconditional commitment to student achievement, trusting students, taking personal risk in mentoring students and addressing abnormal behaviors, and emotional stimulation through communication. Earlier researchers applied House and Baetz's (1979) concepts as the basis for defining teachers' charismatic leadership (Goodboy & Bolkan, 2011;Gunasekare, 2019); thus, teachers' charismatic leadership can be defined based on their vision, personal emotions to attract and motivate students, and influence on students' behavior.…”
Section: Teachers' Charismatic Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient empirical evidence is available to support that teachers are the most crucial in-school factor for student learning (Berry, 2013;Clotfelter et al, 2010). Based on leadership theory, Gunasekare (2019) found that the characteristics of teachers with charismatic leadership include setting tasks for students, unconditional commitment to student achievement, trusting students, taking personal risk in mentoring students and addressing abnormal behaviors, and emotional stimulation through communication. Earlier researchers applied House and Baetz's (1979) concepts as the basis for defining teachers' charismatic leadership (Goodboy & Bolkan, 2011;Gunasekare, 2019); thus, teachers' charismatic leadership can be defined based on their vision, personal emotions to attract and motivate students, and influence on students' behavior.…”
Section: Teachers' Charismatic Leadershipmentioning
confidence: 99%
“…Previous studies have reported the positive role of passion in the entrepreneurial process (Cardon et al, 2015;Huyghe et al, 2016). Gunasekare's (2019) research in the education field demonstrated that teachers with charismatic leadership can stimulate students' positive emotions. Li & Wu's (2019) research showed that teachers can promote students' entrepreneurial passion.…”
Section: Teachers' Charismatic Leadership Entrepreneurial Passion And...mentioning
confidence: 99%
“…As a result of this connection, their followers exhibit increased motivation and need for achievement (House, 1976(House, , 1977. Since teachers are leaders in the classroom (Archer, 1994;Armandi et al, 2003;Goodboy & Bolkan, 2011;Gunasekare, 2019), and CLT suggests that charismatic leaders influence their followers' motivation and need for achievement (House, 1976(House, , 1977, then charismatic teachers may also influence their students' motivation and need for achievement in a classroom setting.…”
Section: Charismatic Leadership Theorymentioning
confidence: 99%